Large-Scale Transposon Mutagenesis of Mycoplasma pulmonis - French, Christopher T. (2008)
To obtain mutants for the study of the basic biology and pathogenic mechanisms of mycoplasmas, the insertion site of transposon Tn4001T was determined for 1,700 members of a library of Mycoplasma pulmonis mutants. After evaluating several criteria for gene disruption, we concluded that 321 of the 782 protein coding regions were inactivated. The dispensable and essential genes of M. pulmonis were compared to those reported for Mycoplasma genitalium and Bacillus subtilis. Perhaps the most surprising result of the current study was that unlike other bacteria, ribosomal proteins S18 and L28 were dispensable. Carbohydrate transport and the susceptibility of selected mutants to UV irradiation were examined to assess whether active transposition of Tn4001T within the genome would confound phenotypic analysis. In contrast to earlier reports suggesting that mycoplasmas were limited in their DNA repair machinery, mutations in recA, uvrA, uvrB and uvrC resulted in a DNA-repair deficient phenotype. A mutant with a defect in transport of N-acetylglucosamine was identified.